Approximation of irrationals - Malvina Baica (International Journal of Mathematics and Mathematical Sciences)
The author uses a new modification of Jacobi-Perron Algorithm which holds for complex fields of any degree (abbr. ACF), and defines it as Generalized Euclidean Algorithm (abbr. GEA) to approximate irrationals.